Nrf2 Induction Re-establishes a Proper Neuronal Differentiation Program in Friedreich’s Ataxia Neural Stem Cells - La Rosa, Piergiorgio; Russo, Marta; D’Amico, Jessica; Petrillo, Sara; Aquilano, Katia; Lettieri-Barbato, Daniele; Turchi, Riccardo; Bertini, Enrico S.; Piemonte, Fiorella (Frontiers in Cellular Neuroscience, 2019)
Frataxin deficiency is the pathogenic cause of Friedreich’s Ataxia, an autosomal recessive disease characterized by the increase of oxidative stress and production of free radicals in the cell. Although the onset of the pathology occurs in the second decade of life, cognitive differences and defects in brain structure and functional activation are observed in patients, suggesting developmental defects to take place during fetal neurogenesis. Here we describe impairments in proliferation, stemness potential and differentiation in neural stem cells isolated from the embryonic cortex of the Frataxin Knockin/Knockout mouse, a disease animal model whose slow-evolving phenotype makes it suitable to study pre-symptomatic defects that may manifest before the clinical onset. We demonstrate that enhancing the expression and activity of the antioxidant response master regulator Nrf2 ameliorates the phenotypic defects observed in neural stem cells, re-establishing a proper differentiation program.